2017
DOI: 10.1056/nejmoa1611391
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Acute Kidney Injury in Critically Ill Children and Young Adults

Abstract: Background The epidemiologic characteristics of children and young adults with acute kidney injury have been described in single-center and retrospective studies. We conducted a multinational, prospective study involving patients admitted to pediatric intensive care units to define the incremental risk of death and complications associated with severe acute kidney injury. Methods We used the Kidney Disease: Improving Global Outcomes criteria to define acute kidney injury. Severe acute kidney injury was defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
711
13
19

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 823 publications
(780 citation statements)
references
References 27 publications
37
711
13
19
Order By: Relevance
“…Severe AKI occurred in 543 (11.6%) patients and is related to an increased risk of death by day 28, increased use and duration of mechanical ventilation and renal replacement therapy. Respiratory and neurologic disorders stood out as the first (38.7%) and second (35.2%) most common co-existing conditions in the critically ill children in this study (15). Therefore, it fits the pattern of AKI development in this study on critically ill children with cerebral palsy.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Severe AKI occurred in 543 (11.6%) patients and is related to an increased risk of death by day 28, increased use and duration of mechanical ventilation and renal replacement therapy. Respiratory and neurologic disorders stood out as the first (38.7%) and second (35.2%) most common co-existing conditions in the critically ill children in this study (15). Therefore, it fits the pattern of AKI development in this study on critically ill children with cerebral palsy.…”
Section: Discussionsupporting
confidence: 72%
“…Several risk factors were associated with severe AKI including transplantation, decreased renal perfusion, the use of nephrotoxic medications, radiocontrast exposure, poor nutrition and glycemic control, and major surgery as the most common findings (15 -17). However, the AWARE study data suggested that children are more likely to survive severe AKI than adults due to greater renal reserves in children (15). It is to be noted that AKI survivor children are at risk for chronic kidney disease, long-term follow-up is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a common and serious disorder associated with considerably high morbidity and mortality [1, 2]. It affects about 1 in 5 hospitalized patients worldwide and has mortality rates of 23.9% in adults and 13.8% in children [3].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of severe AKI conferred an increased risk of mortality by an adjusted odds ratio of 1.77 (95% CI, 1.17-2.68), with a mortality rate of 11% versus 2.5% (P<0.001) in patients without severe AKI. 12 The benefit of including multiple criteria (both serum creatinine and urine output) by which to increase sensitivity was also confirmed, as 67.2% of the patients found to have AKI by oliguria would have been missed if using serum creatinine alone. Strikingly, a significant increase in mortality was also observed (7.8% versus 2.9%, P=0.02) when severe AKI threshold (KDIGO Stage 2 or 3) was achieved due to oliguria compared to creatinine.…”
mentioning
confidence: 90%
“…Strikingly, a significant increase in mortality was also observed (7.8% versus 2.9%, P=0.02) when severe AKI threshold (KDIGO Stage 2 or 3) was achieved due to oliguria compared to creatinine. 12 …”
mentioning
confidence: 99%